Mental Workload and Burnout among Social Work Professionals in Spain: The Protective Role of Psychological Capital and Perceived Social Support. - Muro, Pilar Montañés; Argüello-Gutiérrez, Catalina; Burgos, Ingrit Moya; Hernández, Francisco Lucas Chinchilla (Health & Social Work, 2026)
Social workers are at high risk of suffering from burnout syndrome due to the high work demands and the characteristics of their professional practice, yet there is little research that investigates the predictors and protectors of burnout among this group. This article examined the relationship between mental workload (MWL) and burnout in a sample of Spanish social workers. In addition, it analyzed whether psychological capital (PC) and perceived social support (PSS) mediate this relationship. For this purpose, 270 social work professionals completed an online questionnaire that collected information on MWL, PC, PSS, and burnout. The results show that MWL predicts burnout, and that PC and PSS only partially mediate the relationship between MWL and burnout. However, the direct effect of MWL on burnout remains significant, suggesting that other factors may also be involved. Nevertheless, PC and PSS act as internal and external protective factors, respectively, of burnout. This work underlines the importance of implementing interventions to strengthen personal resources and social support as a way to prevent burnout in social workers.